Hypoxia inducible factor‐1α‐induced interleukin‐33 expression in intestinal epithelia contributes to mucosal homeostasis in inflammatory bowel disease. (6th December 2016) - Sun, M.; He, C.; Wu, W.; Zhou, G.; Liu, F.; Cong, Y.; Liu, Z.
Summary: Intestinal epithelial cells (IECs), an important barrier to gut microbiota, are subject to low oxygen tension, particularly during intestinal inflammation. Hypoxia inducible factor‐1α (HIF‐1α) is expressed highly in the inflamed mucosa of inflammatory bowel disease (IBD) and functions as a key regulator in maintenance of intestinal homeostasis. However, how IEC‐derived HIF‐1α regulates intestinal immune responses in IBD is still not understood completely. We report here that the expression of HIF‐1α and IL‐33 was increased significantly in the inflamed mucosa of IBD patients as well as mice with colitis induced by dextran sulphate sodium (DSS). The levels of interleukin (IL)−33 were correlated positively with that of HIF‐1α. A HIF‐1α‐interacting element was identified in the promoter region of IL‐33, indicating that HIF‐1α activity regulates IL‐33 expression. Furthermore, tumour necrosis factor (TNF) facilitated the HIF‐1α‐dependent IL‐33 expression in IEC. Our data thus demonstrate that HIF‐1α‐dependent IL‐33 in IEC functions as a regulatory cytokine in inflamed mucosa of IBD, thereby regulating the intestinal inflammation and maintaining mucosal homeostasis. Abstract : HIF‐1a and IL‐33 are highly expressed in intestinal epithelial cells of IBD patients. HIF‐1a regulates IL‐33 expression through the HIF‐1α‐interacting element in the promoter region of IL‐33. TNF regulates both HIF‐1a and IL‐33 expressions, and, particularly, induces IL‐33 expression in a HIF‐1α‐dependent manner.